Quantification of oxyresveratrol analog trans-2,4,3',5'-tetramethoxystilbene in rat plasma by a rapid HPLC method: Application in a pre-clinical pharmacokinetic study - Lin, H.-S. (2014)
10.1002/bmc.1454